Lipschitz Stability in Terms of Two Measures for Kurzweil Equations and Applications - Yingying Wang; Zhinan Xia (Mathematics, 2023)
For generalized ordinary differential equations, sufficient criteria are given for the Lipschitz stability in terms of two measures of the trivial solutions. As an application, we apply our main results by studying the Lipschitz stability for measure differential equations and impulsive differential equations. Compared to the classical ones, the conditions here regarding the functions are more general.